One Idea for Preparation of Solidified Oxide Eutectic Film by Controlling Chemical Reaction between the Melt and Substrate - Kyosuke Seya; Shunkichi Ueno; Byung-Koog Jang (Chemical and Materials Sciences: Developments and Innovations Vol. 10, 2025)
A preparation method for solidified eutectic film with good adhesion between the film and substrate by controlling the chemical reaction between the base material and the melt is described. As an example, Al2O3-HfO2 eutectic solidification film was formed on a SiC substrate. Al2O3-HfO2 eutectic EBC film is prepared by the optical zone melting method on the silicon carbide substrate. At high temperatures, a small amount of silicon carbide decomposes into silicon and carbon. The components of Al2O3 and HfO2 in the molten phase also react with the free carbon. The Al2O3 phase reacts with free carbon, leading to the formation of AlO vapor species. The composition of the molten phase becomes HfO2 rich from the eutectic composition. HfO2 phase also reacts with the free carbon and HfC phase is formed on the silicon carbide substrate; then a high-density intermediate layer is formed. The adhesion between the intermediate layer and the substrate is excellent by an anchor effect. When the solidification process is finished before all of the HfO2 phase is reduced to the HfC phase, HfC-HfO2 functionally graded layer is formed on the silicon carbide substrate and the Al2O3-HfO2 eutectic structure grows from the top of the intermediate layer. This process can be applied to different oxide eutectic systems that include HfO2 and/or ZrO2 phase such as CaZrO3-ZrO2 and Ln2Zr2O7-ZrO2 eutectic systems.